SISTEM INFORMASI SECARA ONLINE TUGAS AKHIR MAHASISWA JURUSAN TEKNOLOGI INFORMASI FAKULTAS TEKNOLOGI INFORMASI DAN KOMUNIKASI - Atmoko Nugroho; Nur Wakhidah; Bernadus Very Christioko (Jurusan Teknologi Informasi Universitas Semarang, 2015)
Tugas Akhir is the last stage that will surely passed by students to earn college scholarship. And one of the activities in the field of data administration is to manage file of Tugas Akhir, especially for the submission title and Coordinators of Tugas Akhir. Coordinators are often difficult to check the title of Tugas Akhir, if it has been filed or is pending, and the difficulties in monitoring the load guidance from their Supervisor of Tugas Akhir. This also forms the basis for making an Information System of Tugas Akhir (Sistem Informasi Tugas Akhir) with the aim of assisting Jurusan Teknologi Informasi and students take this.Sistem Informasi Tugas Akhir called SITA also be made online this method applying Prototype system development. Prototype method according to Pressman has experienced several stages, namely: collection needs (listen to customers), design (built / REVISE mock-up) and evaluation of prototypes (customer test-drives a mock-up). The collection needs to be done, among others, the acquisition of data. The data used in this information system is the data of Tugas Akhir of Jurusan Teknologi Informasi. The next stage in the design, researchers uses planning tool in the form of Unified Modeling Language system (UML) and developed using the PHP programming language.System of web-based information created a purpose to be accessible without being restricted by time and place, whereas the benefit derived is facilitated student and coordinator duties in management of Tugas Akhir.